2021
DOI: 10.1057/s41599-021-00738-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of content knowledge on the adoption of a critical curriculum model by history teachers-in-training

Abstract: This work analyses the impact of disciplinary training on future Primary and Secondary School teachers’ decision to adopt a critical approach for teaching history. To do this, we will use a two-phase mixed methodological approach (quantitative and qualitative) to analyse the relationship between their previous training and the use of epistemological and psycho-pedagogical objectives and paradigms as outlined in a critical curriculum model. As regards data collection in the first phase, a closed questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…On the other, there is now classic research on teachers' beliefs concerning the curriculum, teaching, and learning, which in the case of history has essentially been explored in studies focused on the difficulties involved in implementing inquiry-based learning-essential for developing the capacity for historical thinking-in the classroom. Some recent studies can be found in the Spanish context, such as Colomer et al (2021), Parra-Monserrat et al (2021), and Gómez-Carrasco et al (2022). However, the pioneering method of this research has complicated the possibility of contrasting its results with those of previous studies.…”
Section: Introductionmentioning
confidence: 88%
“…On the other, there is now classic research on teachers' beliefs concerning the curriculum, teaching, and learning, which in the case of history has essentially been explored in studies focused on the difficulties involved in implementing inquiry-based learning-essential for developing the capacity for historical thinking-in the classroom. Some recent studies can be found in the Spanish context, such as Colomer et al (2021), Parra-Monserrat et al (2021), and Gómez-Carrasco et al (2022). However, the pioneering method of this research has complicated the possibility of contrasting its results with those of previous studies.…”
Section: Introductionmentioning
confidence: 88%
“…Este cambio es mucho más acusado entre los participantes del grupo de Artes y Humanidades, lo que, a priori, podría indicar que una formación más profunda en Historia y su didáctica dota a los estudian-tes del Grado en Maestro/a de un bagaje y un entramado teórico para enunciar un discurso más crítico sobre la educación histórica y sus potenciales usos. Además, esta mayor presencia de respuestas alternativas es coherente con la menor presencia de respuestas ligadas a modelos tradicionales, lo que nos permite apreciar una cierta consistencia en los discursos de los estudiantes en la línea planteada por otros estudios recientes (Borja y Parra, 2017;Miguel-Revilla y Fernández, 2017;Miguel-Revilla, Carril y Sánchez-Agustí, 2017;Parra y Morote, 2020;Parra, Fuertes, Asensi y Colomer, 2021).…”
Section: Representaciones Y Usos De La Historiaunclassified
“…Este recorrido de aprendizaje en formación docente (conocimiento disciplinar profundo a nivel epistemológico y conocimiento didáctico disciplinar amplio y práctico) puede desplegarse en dos vías, según el grado de aprovechamiento del mismo y, posiblemente, según la riqueza de la formación histórica previa que disponga el profesorado en formación. Esas dos vías, atendiendo a la conceptualización de modelos curriculares o didácticos en enseñanza de la historia (Parra et al, 2021;Rozada, 1997) pasan por superar el modelo técnico tradicional apostando bien por un modelo práctico, que prioriza los cambios procedimentales y cognitivos en el aprendizaje histórico, o bien ir más allá y asumir un modelo crítico que, sin renunciar a la dimensión metodológica, prima la problematización de los contenidos y sus usos y finalidades para formar en ciudadanía democrática.…”
Section: Fundamentos Teóricos: Competencias De Pensamiento Histórico ...unclassified
“…En primer lugar el mayor nivel depende del grado de aprovechamiento de la formación teórico-práctica del MAES. En dicha formación, como se señaló, tiene particular relevancia el cambio epistemológico en la representación de la historia y de su enseñanza que evidencien, reflexionando sobre los contenidos y las finalidades de la misma; dicho cambio es en sí mismo un recorrido de aprendizaje que puede ser más efectivo en quienes son capaces de aprovechar su formación disciplinar previa en Historia, cuestión evidenciada en investigaciones previas (Parra & Morote, 2020;Parra et al, 2021). De hecho entre quienes muestran niveles declarativos más básicos la presencia de graduados en otras disciplinas que no son Historia (Historia del Arte y Geografía) es mayor; a su vez, son más los graduados en Historia que manifiestan niveles aplicativos.…”
Section: Discusión Y Conclusionesunclassified